Market power and bank profitability: Evidence from Montenegro and Serbia - Zoran Grubišić; Sandra Kamenković; Tijana Kaličanin (Journal of Central Banking Theory and Practice, 2022)
This study investigates the relationship between profitability and market power in the banking sector using data from the financial reports of the banks that operated in Serbia and Montenegro, covering the period from the first quarter of 2010 to the last quarter of 2019. In order to investigate this relationship, determinants of bank profitability are split between internal and external. As the external determinants, selected ratios of concentration were calculated and used in order to measure market power. The total of sixteen panel regression models were applied, eight for each country. The results indicate that variations of return on assets and return on equity in Serbia can be explained by the variations of the ratios of concentration. On the other hand, results of the panel regression model applied for the banking sector of Montenegro does not give enough argument to support such explanation, and bank profitability can be explained by bank efficiency to some extent.
Keywords: G21; E58; L10; 330; banking sector; bank profitability; market power; competition